Unani Treatment Improved Fibrosis in Decompensated Cirrhosis of Liver: A Case Series - Siddiqui, Mohammad Akhtar; Ansari, Shabnam (Journal of Advances in Internal Medicine, 2017)
Introduction At present, liver transplantation remains the only curative option for the patients with cirrhosis and end-stage liver diseases. The survival rate and recurrent diseases remains the major issue in the patient post-transplantation. Unani medicine is one of the oldest traditional system of medicine, has been treating chronic liver diseases and cirrhosis [Talayyaful-Kabid] since centuries. The purpose of our study was to assess the impact of Unani treatment in decompensated cirrhosis and collect data to warrant further clinical trials. Case presentation We have conducted a case series with three patients of decompensated cirrhosis and portal hypertension. Cases were confirmed by fibroscan and ultrasound and treated with Unani treatment orally for 3 months. Results were evaluated based on fibroscan, liver function test, EQ5D and TTO-TIME [tradeoff question]. Conclusions Significant improvement in liver function test, fibrosis and quality of life were achieved in the patients. We reviewed the literature related to the herbal constituents of chief medicines used for the treatment in this case. The herbs have been proved for its potential anti-oxidative, anti-inflammatory, hepatoprotective, immuno-modulator and antiviral activities, suggesting plausible mechanisms of action in these cases. The preliminary findings indicate the potential therapeutic role of Unani treatment in decompensated cirrhosis. Clinical trials should be conducted to explore the further therapeutic potential of Unani treatment in decompensated cirrhosis.